A Review Article On Nirjivanukaran W.S.R To Sterilization - singh, Ranjit; priya, Upasana (International Research Journal of Ayurveda & Yoga, 2020)
The term “sterilization” means removal or killing of microorganisms from the surface of the object. In Ayurveda Sterilization is also known as “Nirjivanukaran”. The Acharya’s mentioned thousands year back that the Nirjivanukaran is important before commencement of any surgical procedure. The different methods of sterilizations adopted by Acharya’s were Dhupana Karama, Vrana Prakshalna, Shastra Tapan, sterilization of Kumaragara, Sootikagaara, Vranitagaara, water filteration methods like Hansodaka, and use of flowers in water purification. The sterilization is done to control infection, sometimes infection spreads in large scale. In history we have many such examples which shows death of population on large scale due to infection i.e. plaque. The disease like plaque killed approximately 75-200 million of people with no cure. The infection claims millions of death every year which can be prevented by adopting proper sterilization methods. In 21st century modern science led to invention of many vaccines, preservatives, chemical formulations, newer techniques of air fumigation, sterilization by various physical & chemical methods and water filtration methods. In this article we have discussed many such methods. In this article attempt is made to know ancient techniques of sterilization in Ayurveda and to understand basic concepts & proper techniques of existing sterilization methods.